The Cawdor estates in south-west Wales in the nineteenth century. - John Edward Davies (2008)
This work is a consideration of the role and influence of the Cawdor estate in southwest Wales in the nineteenth century. The estate was by far the largest in this remote area, and consequently its influence spread far and wide. The fundamental belief in the stability of the land to produce an income for the owner was at its zenith when this study commences. However, as the nineteenth century progressed this belief was eroded by a combination of democratic, political and economic forces, until, by the first decade of the twentieth century, it seemed that all that was left for the majority of landowners was to sell-off their estates and abandon their so recently unassailable position of power and influence. This study examines the role of the Cawdor estate in this century-long demise and investigates how the Earls Cawdor reacted to the erosion of their influence. As such the study examines the main sources of their wealth-the agricultural estate, and to a lesser extent the industrial estate. As a major part of the agricultural estate was let out to tenant fanners, the treatment of tenants takes precedence, since without their rent the Cawdors would have enjoyed no life of conspicuous wealth. Exploitation of mineral wealth also assisted in swelling the Cawdor coffers; thus an examination of the industrial estate is undertaken to ascertain the extent of such involvement. As a concomitant to the expansion of the Cawdors' industrial estate, their role in the development of the infrastructure of south-west Wales will also come under scrutiny. As Anglican Christian paternalists the Cawdors' responsibility towards the established church and its revival and to the moral well-being of the poor via their education, will be explored. These areas brought the Cawdors into conflict with the fast-growing nonconformist denominations and the accompanying political Liberalism, and their reaction to these, and to the growing call for the new phenomenon of democracy are examined to ascertain how, if at all, the Cawdors were able to change their paternalist philosophy in order to cope with the newer political and religious forces. As leaders of the two counties of Pembrokeshire and Cannarthenshire their input to the political arena, both at a local level as Lords Lieutenant and magistrates, and at national levels as Welsh MPs, will establish their vital contribution (or not) to the political well-being of Wales. Finally, a picture will be drawn of the Cawdors' leisure pursuits in the countryside-hunting and shooting, horse racing and yachting-and of their life in the Metropolis, where much of their income from the estates was spent, whether at the theatre or in the purchase of art with which they adorned their homes. In conclusion, the impact that the Cawdors wrought on the immediate locality of south-west Wales and further afield will be assessed in order to decide whether they were a force for the good or otherwise.